Serum Antioxidant Vitamins (A, E, C), Selenium and Melondialdehyde Levels in Workers Exposed to Aerosol - Karatas, Fikret; Tug, Tuncer; Konar, Vahit (Bilimsel Tip Publishing House, 2008)
We investigated serum antioxidant vitamins (A, E and C), selenium (Se) and malondialdehyde (MDA) levels in subjects who were exposed to aerosol (dye products) via inhalation, as compared to unexposed control subjects. Twenty paint workers and 22 controls participated for this study. The serum vitamins (A, E, C) MDA and Se levels in both groups were measured using HPLC. The levels of vitamin A, E and selenium levels were significantly decreased in workers (p< 0.05), while serum MDA levels were significantly increased ( p< 0.005), and the levels of vitamin C were almost the same in dye paint workers as in the control subjects (p> 0.05). Free radical activity (oxidative stress) levels were increased whereas non-enzymatic parameters were decreased in painters exposed to aerosol inhalation compared to controls. To determine whether the observed results were related to endogen antioxidant deficiency or vitamin deficiency or Se levels deficiency, or whether another unknown agent is involved requires further investigation.
Keywords: aerosol; vitamins; selenium; HPLC